MUHAMMADIYAH UNIVERSITY OF PURWOKERTO'S GLOBAL RESEARCH IMPACT: A BIBLIOMETRIC ANALYSIS - Saky, Sheikh Abu Toha Md; Isam, Md. Nurul (IAIN Kendari, 2024)
This study provides a concise overview of a comprehensive study focused on Muhammadiyah University of Purwokerto (UMP), delving into its contributions to the global research landscape. The primary aim is to unravel UMP's global research impact, encompassing scientific production, citation patterns, collaborative networks, and evolving research themes. By utilizing a dataset of 480 documents from 247 diverse sources, the study aims to provide a nuanced understanding of UMP's role in shaping global research narratives. Employing bibliometric analysis, the study utilizes the Scopus database for data extraction spanning 2010 to September 2023. The dataset undergoes meticulous pre-processing to ensure accuracy. Biblioshiny software facilitates a comprehensive analysis, examining annual growth rates, citation patterns, collaborative dynamics, and prevalent research themes. The analysis reveals a dynamic research landscape, characterized by an annual growth rate of 30.86%. Noteworthy trends in annual scientific production and citation impact are unveiled, showcasing the evolving nature of UMP's research impact. The study identifies influential sources, prolific authors, and global collaboration patterns, offering insights into UMP's contributions to diverse research areas. This study sheds light on UMP's dynamic growth trajectory and its impact on global research narratives. The interconnectedness, revealed through bibliometric analysis, underscores UMP's commitment to advancing knowledge. The findings contribute to a comprehensive understanding of UMP's research performance, collaborative efforts, and emerging trends, positioning the institution on the global academic stage.